Tense-aspect in English and Tamil verbs a contrastive analysis - Miranda, Laz Peter 1934-
Verbs or verb expressions in predicate position, positive form, active voice, indicative mood, and third person singular are the only forms considered in the constructive analysis of tense-aspect in English and Tamil verbs. The morphological constituents, the syntactical arrangements and the grammatical meanings of these verbs/verb expressions and their arrangements were considered in the description of the verb structures of English and Tamil. Patterns in English and Tamil are presented for comparison to identify the similarities and differences between English and Tamil Tense-Aspect Structures.
Thesis (M.A.T. English)--University of the Philippines.
Keywords: English language -- Verb; Tamil language